Does this apply here?: Ethical considerations in transnational supervision settings. Issue 4 (19th May 2021) - Schultz, Tammy; Yoo, Hana; Kellums Baraka, Mandy; Watson, Terri
ABSTRACT: Most of the ethical decision making literature that guides mental health practice comes from the Western hemisphere. The well-meaning application of Western values in supervision can result in the intrusion of ethical standards that may not match the context and lacks sensitivity. In this qualitative study, researchers explored the supervisory experiences of 25 mental health professionals of 14 different nationalities, navigating complex ethical challenges in supervision practice in 17 countries. Using thematic analysis, several well-supported themes emerged. Recommendations for practice include the importance of supervisors taking primary responsibility for initiating cultural discussions and fostering a collaborative approach to navigating complex cultural dilemmas.